Secure And Affordable Stratified Housing Criteria Model In Malaysia - Ha, Chin Yee (2023)
The middle-income group occupies most of the total population in Malaysia. The demand towards affordable stratified houses was increasing due to the basic needs for shelter. Besides, the security level in housing areas is getting attention from house buyers when surveying homes. Therefore, this study was intended to identify the security criteria that should be emphasized and implemented in affordable stratified housing, which can improve the security level and maintain the affordability of the middle-income group or M40 group at the same time. Since this research study was focusing on the M40 group in Malaysia, thus, a quantitative method was employed to carry out the research and there are 300 respondents involved in this research. Moreover, the findings of study showed that the six security criteria which are surveillance, access control, territoriality, target hardening, sense of community and management and maintenance were significantly impacted affordable secure homes. Furthermore, the moderation effect of government intervention between security criteria implementation and affordable secure homes can enhance the effects of security criteria on the housing security level. Therefore, this research has developed a conceptual framework for the construction industry as a practitioners’ reference. In a nutshell, future practical implications and conclusions were provided to facilitate the implementation of security criteria in affordable housing development in the Malaysia housing market.